Food risk characterization from exposure to persistent organic pollutants and metals contaminating eels from an Italian lake - Chiesa, Luca Maria; Zanardi, Emanuela; Nobile, Maria; Panseri, Sara; Ferretti, Enrica; Ghidini, Sergio; Foschini, Stefano; Ianieri, Adriana; Arioli, Francesco (Food Additives & Contaminants: Part A, 2019)
Monitoring environmental contaminants in edible animal species is important for the assessment of environmental quality and for food safety as well. In this study, the occurrence of 2,3,7,8 dioxins, and furans, dioxin-like polychlorinated biphenyls, six non-dioxin-like polychlorinated biphenyl indicators (ndl-PCBs), seven polybrominated diphenylethers (PBDEs), four polycyclic aromatic hydrocarbons (PAHs) and four metals (As, Hg, Ni, Pb) was evaluated in 90 European eels (Anguilla anguilla) from Lake Garda. The results on eel samples showed a frequent contamination of dl-PCBs, found at concentrations higher than the maximum limit (ML) provided by European Union in 41 % of the eels. Two PBDE congeners (BDE 47 and BDE 99) were detected in almost all the samples. The contamination by PAHs was found negligible; only one sample had a high concentration of benzo[a]pyrene. Concerning metals, Pb showed concentrations higher than the maximum level (ML) in 77% of the samples, while Ni content could be a cause of acute toxicity due to dermatitis. Extreme consumers (95th percentile) are subjected to an actual risk attributable to dioxins, furans, and mainly dl-PCBs and PBDEs. The contamination of Lake Garda eels is therefore a matter of concern and a constant monitoring of the pollution levels of its freshwater is mandatory.